In-vivo evaluation of silk fibroin small-diameter vascular grafts: state of art of preclinical studies and animal models - Settembrini, Alberto; Buongiovanni, Gianluca; Settembrini, Piergiorgio; Alessandrino, Antonio; Freddi, Giuliano; Vettor, Giulia; Martelli, Eugenio (Frontiers in Surgery, 2023)
Autologous vein and artery remain the first choice for vascular grafting procedures in small-diameter vessels such as coronary and lower limb districts. Unfortunately, these vessels are often found to be unsuitable in atherosclerotic patients due to the presence of calcifications or to insufficient size. Synthetic grafts composed of materials such as expanded polytetrafluoroethylene (ePTFE) are frequently employed as second choice, because of their widespread availability and success in the reconstruction of larger arteries. However, ePTFE grafts with small diameter are plagued by poor patency rates due to surface thrombogenicity and intimal hyperplasia, caused by the bioinertness of the synthetic material and aggravated by low flow conditions. Several bioresorbable and biodegradable polymers have been developed and tested to exploit such issues for their potential stimulation to endothelialization and cell infiltration. Among these, silk fibroin (SF) has shown promising pre-clinical results as material for small-diameter vascular grafts (SDVGs) because of its favorable mechanical and biological properties. A putative advantage in graft infection in comparison with synthetic materials is plausible, although it remains to be demonstrated. Our literature review will focus on the performance of SF-SDVGs in vivo, as evaluated by studies performing vascular anastomosis and interposition procedures, within small and large animal models and different arterial districts. Efficiency under conditions that more accurately mime the human body will provide encouraging evidence towards future clinical applications.